PAMAM Dendrimer Nanomolecules Utilized as Drug Delivery Systems for Potential Treatment of Glioblastoma: A Systematic Review - Fana, Michael (Int J Nanomedicine, 2020)
Glioblastoma (GB) is a grade IV astrocytoma that maintains a poor prognosis with respect to current treatment options. Despite major advancements in the fields of surgery and chemoradiotherapy over the last few decades, the life expectancy for someone with glioblastoma remains virtually unchanged and warrants a new approach for treatment. Poly(amidoamine) (PAMAM) dendrimers are a type of nanomolecule that ranges in size (between 1 and 100 nm) and shape and can offer a new viable solution for the treatment of intracranial tumors, including glioblastoma. Their ability to deliver a variety of therapeutic cargo and penetrate the blood–brain barrier (BBB), while preserving low cytotoxicity, make them a favorable candidate for further investigation into the treatment of glioblastoma. Here, we present a systematic review of the current advancements in PAMAM dendrimer technology, including the wide spectrum of dendrimer generations formulated, surface modifications, core modifications, and conjugations developed thus far to enhance tumor specificity and tumor penetration for treatment of glioblastoma. Furthermore, we highlight the extensive variety of therapeutics capable of delivery by PAMAM dendrimers for the treatment of glioblastoma, including cytokines, peptides, drugs, siRNAs, miRNAs, and organic polyphenols. While there have been prolific results stemming from aggressive research into the field of dendrimer technology, there remains a nearly inexhaustible amount of questions that remain unanswered. Nevertheless, this technology is rapidly developing and is nearing the cusp of use for aggressive tumor treatment. To that end, we further highlight future prospects in focus as researchers continue developing more optimal vehicles for the delivery of therapeutic cargo.